China's America : the Chinese view the United States, 1900-2000 - Li, Jing, 1961- (SUNY series in Chinese philosophy and culture., 2011)
What do the Chinese think of America? Why did Jiang Zemin praise the film Titanic? Why did Mao call FDR's envoy Patrick Hurley "a clown?" Why did the book China Can Say No (meaning "no" to the United States) become a bestseller only a few years after a replica of the Statue of Liberty was erected during protests in Tiananmen Square? Jing Li's fascinating book explores Chinese perceptions of the United States during the twentieth century. As Li notes, these two very different countries both played significant roles in world affairs and there were important interactions between them. Chinese views of the United States were thus influenced by various and changing considerations, resulting in interpretations and opinions that were complex and sometimes contradictory. Li uncovers the historical, political, and cultural forces that have influenced these alternately positive and negative opinions. Revealing in its insight into the twentieth century, China's America is also instructive for all who care about the understandings between these two powerful countries in the twenty-first century. -- From the Back Cover.